Monarchische Herrschaftsformen der Vormoderne in transkultureller Perspektive - Drews, Wolfram; Flüchter, Antje; Dartmann, Christoph; Gengnagel, Jörg; Höfert, Almut; Kolditz, Sebastian; Oesterle-El Nabbout, Jenny Rahel; Schilling, Ruth; Schwedler, Gerald (De Gruyter, 2015)
This volume looks acrossdifferent periodsto develop a comparative analysis of different monarchies with respect to the function of their political systems. The studies focus on elite groups, on strategies of sacralization as pretexts to generate and perpetuate the legitimacy of monarchies, and on strategies to establish various forms of historical memory. Wolfram Drews, University of Münster, Germany, Antje Flüchter, University of Bielefeld, Germany, et al.
Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic books; Aufsatzsammlung; Geschichte; Kulturvergleich; Monarchie